Popping the Positive Illusion of Financial Responsibility Can Increase Personal Savings: Applications in Emerging and Western Markets. (May 2021) - Garbinsky, Emily N.; Mead, Nicole L.; Gregg, Daniel
People around the world are not saving enough money. The authors propose that one reason people undersave is because they hold the positive illusion of being financially responsible. If this conjecture is correct, then deflating this inflated self-view may increase saving, as people should become motivated to restore perceptions of financial responsibility. After establishing that people do hold the illusion of financial responsibility, the authors developed an intervention that combats this self-enhancing bias by triggering people to recognize their frequent engagement in superfluous spending. This superfluous-spender intervention increased saving by enhancing people's motivation to restore their diminished perceptions of financial responsibility. Consistent with theorizing, the intervention increased saving only when superfluous spending was under one's control and among those who were motivated to perceive themselves as financially responsible. In addition to increasing saving in Western countries, the superfluous-spender intervention increased saving of earned income and a financial windfall over time among chronically poor coffee growers in rural Uganda. Collectively, this work shows that people view their financial responsibility through rose-colored glasses, which can undermine their financial well-being. It also endows stakeholders with a simple, practical, and inexpensive intervention that offsets this bias to increase personal savings.